Improvements of electrochemical water splitting efficiency by using economically viable Co/CoPs/TiO₂/NiF electrocatalysts - Kulathunga Mudiyansele, Soorya Dananjaya Bandara Kulathunga (Cranfield University, 2024)
The drive for sustainable energy solutions has led to the search for efficient and cost-effective electrocatalysts for green hydrogen production via electrochemical water splitting (EWS). This study addresses the limitations of precious metal- based catalysts by investigating alternative, earth-abundant materials. This research introduces a novel Co/CoPs(240)/TiO₂/NiF electrocatalyst, synthesized using deep eutectic solvent (DES)-mediated electrodeposition of Co and cobalt phosphides (CoPs) on TiO₂-coated nickel foam (NiF) substrate. Electrophoretic deposition of TiO₂ nanoparticles was successfully applied to NiF, resulting in a smooth and even surface. On this TiO₂-coated substrate, subsequent Co/CoPs deposition produced unique hexagonal and cauliflower-like structures with a uniform distribution of Co and P. Energy dispersive X-ray spectroscopy (EDX), scanning electron microscopy (SEM), and X-ray diffraction (XRD) were used to confirm these features. Optimizing the Co/CoPs deposition times significantly reduced the hydrogen evolution reaction (HER) overpotential to 34.42 ± 4.2 mV at 10 mA cm⁻² in 1 M KOH. Remarkably, the Co/CoPs(240)/TiO2/NiF catalyst required only 27.43 mV with a Tafel slope of 48.35 mV dec⁻¹. Stability tests demonstrated minimal performance degradation after 5000 cycles and 40 hours of operation, demonstrating excellent durability. This optimized catalyst outperformed Co/CoPs(240)/NiF, commercial 10% Pt/C electrodes, and other reported catalysts. The oxygen evolution reaction (OER) performance also highlighted the catalyst's efficiency, with an overpotential of 331.70 mV at 10 mA cm⁻² in 1 M KOH and a Tafel slope of 73.96 mV dec⁻¹. Stability tests revealed minimal performance degradation after 1000 cycles. Furthermore, a full water electrolyser system using Co/CoP(240)/TiO2/NiF electrodes achieved a total voltage of 1.612 V at 10 mA cm⁻², indicating the practical viability of the optimized electrodes for water splitting applications. The remarkable performance of the Co/CoPs(240)/TiO₂/NiF electrode is primarily due to the presence of the TiO₂ layer, which enhances the surface area and acts as a catalyst promoter through synergistic effects and enhanced charge transfer kinetics. This research suggests that incorporating an intermediate TiO₂ layer can promote the catalytic activity of other catalysts as well. In conclusion, this study presents an effective and economical alternative to noble metal-based electrocatalysts for water splitting. By integrating TiO₂ with Co/CoPs on a NiF substrate, the research advances the development of high-performance, low-cost catalysts and contributes to the sustainable production of green hydrogen.
Jiang, Ying - Associate Supervisor
Keywords: Deep eutectic solvent-mediated electrodeposition; Electrophoretic deposition of TiO₂; High-performance electrocatalysts